2015
DOI: 10.3329/jpsb.v5i1.23884
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between intralesional Dexamethasone and oral Prednisolone in the treatment of Infantile Hemangioma

Abstract: Background: Infantile Hemangioma (IH) is one of the most common childhood neoplasm. Current treatments for children with endangering Infantile Hemangioma are limited, and include primarily oral corticosteroid which has many systemic adverse effects. Furthermore, approximately one third of IH does not respond to oral steroids, prompting active investigations for new treatments.Objective: To compare the efficacy, side effects, and influencing factors of oral Prednisolone and intralesional Dexamethasone (IL) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…However, none of the side effects was persistent. Observed side effects during treatment period were shown in (Table 4) Infantile Hemangioma is one of the most misdiagnosed and maltreated clinical problems in Bangladesh [7]. Numerous reports regarding successful treatment of hemangioma by direct Intralesional steroids have appeared in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the side effects was persistent. Observed side effects during treatment period were shown in (Table 4) Infantile Hemangioma is one of the most misdiagnosed and maltreated clinical problems in Bangladesh [7]. Numerous reports regarding successful treatment of hemangioma by direct Intralesional steroids have appeared in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…"Recent study revealed intralesional injection of Triamcinolone acetonide in periorbital Infantile Hemangioma was an effective and safe method of treatment with minimal adverse effects eg. Temporary subcutaneous atrophy" [9]. "Unlike oral prednisolon, intralesional Triamcinolone acetonide is devoid of systemic side effects like impaired growth, weight gain, cushingoid facies, hypertension etc" [9].…”
Section: Introductionmentioning
confidence: 99%
“…Temporary subcutaneous atrophy" [9]. "Unlike oral prednisolon, intralesional Triamcinolone acetonide is devoid of systemic side effects like impaired growth, weight gain, cushingoid facies, hypertension etc" [9]. "Prospective data on corticosteroid therapy are lacking, and no consensus exists regarding the optimal treatment regimen and response rate" [8,7].…”
Section: Introductionmentioning
confidence: 99%